PENERAPAN SENAM OTARIA SEBAGAI ESSENTIAL MIDWIFERY CARE PADA IBU POST PARTUM DI DESA AWANG BANGKAL BARAT KABUPATEN BANJAR - Januarsih; Kirana, Rita; suhrawardi; Nurlaili, Anis (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Perineal tears are among the most common complications experienced by postpartum mothers. A preliminary survey in Awang Bangkal Barat Village revealed that approximately 45% of postpartum mothers suffered perineal tears. Management has primarily focused on pharmacological therapy and general education, with limited structured non-pharmacological interventions. This PKM aimed to introduce and implement Otaria exercise as essential midwifery care to accelerate perineal wound healing, improve maternal knowledge and skills, and enhance family involvement. Conducted over four months (April–July 2025), the program involved preparation, socialization, facilitator training (midwives/cadres), group exercise, home visits, and monitoring. Participants were 10 postpartum mothers selected based on inclusion criteria. Evaluation was carried out using pre-test, post-test, and skill observations. Maternal knowledge increased from 42% to 78%, while skills improved from 50% to 70%. Average attendance reached 80%, with most mothers practicing routinely at home. Perineal pain complaints decreased from 75% to 30%. Outputs included a leaflet, video tutorial, scientific publication, and documentation. Otaria exercise is effective as a non-pharmacological intervention to accelerate perineal wound healing, enhance knowledge, skills, and adherence, and strengthen family support. This program is recommended for integration into community-based midwifery services.